Rationality of Use of Analgetic-Antipyretic Medicines in Northern Region Primary Health Centre of Kediri City - Hanie Kusuma Wardani; Krisogonus Ephrino Seran; Elisa Nur Farida (Universitas STRADA Indonesia, 2020)
One of the efforts carried out by the national rational drug use program is health services that ensure safety, effectiveness, and affordable costs for people who receive or receive treatment. It is said that the use of drugs is rational if the patient gets treatment according to clinical needs, the dose is as needed, the drug can be used for a sufficient period of time and at affordable costs. This study aims to determine the rationality of the use of analgesic-antipyretic drugs in the Northern Region Primary Health Centre of Kediri City which includes: right indication, right patient, right drug, right dose, and alert for drug side effects. This study is a descriptive study conducted by retrospective observation and data collection by looking at prescriptions and medical record data supported by interviews with pharmacists. Based on the results of the research in the Northern Region Primary Health Centre of Kediri City, it can be found that the use of analgesic-antipyretic drugs in 304 samples was obtained paracetamol 33.88%, paracetamol liquid 18.42%, Alpara 10.20%, ibuprofen 12.17%, acid mefenamic 8.88%, diclofenac sodium 7.24%, piroxicam 4.93%, and aspirin 4.28%. The percentage of rationality of using analgesic-antipyretic drugs in the Northern Region Primary Health Centre of Kediri City, got the results, namely: right indication, right patient, right drug, right dose, and alert for drug side effects by 100%.